Improved White Matter Cerebrovascular Reactivity after Revascularization in Patients with Steno-Occlusive Disease - McKetton, L.; Venkatraghavan, L.; Rosen, C.; Mandell, D.M.; Sam, K.; Sobczyk, O.; Poublanc, J.; Gray, E.; Crawley, A.; Duffin, J.; Fisher, J.A.; Mikulis, D.J. (American Journal of Neuroradiology, 2019)
BACKGROUND AND PURPOSE: One feature that patients with steno-occlusive cerebrovascular disease have in common is the presence of white matter (WM) lesions on MRI. The purpose of this study was to evaluate the effect of direct surgical revascularization on impaired WM cerebrovascular reactivity in patients with steno-occlusive disease.MATERIALS AND METHODS: We recruited 35 patients with steno-occlusive disease, Moyamoya disease (n = 24), Moyamoya syndrome (n = 3), atherosclerosis (n = 6), vasculitis (n = 1), and idiopathic stenosis (n = 1), who underwent unilateral brain revascularization using a direct superficial temporal artery–to-MCA bypass (19 women; mean age, 45.8 ± 16.5 years). WM cerebrovascular reactivity was measured preoperatively and postoperatively using blood oxygen level–dependent (BOLD) MR imaging during iso-oxic hypercapnic changes in end-tidal carbon dioxide and was expressed as %Δ BOLD MR signal intensity per millimeter end-tidal partial pressure of CO2.RESULTS: WM cerebrovascular reactivity significantly improved after direct unilateral superficial temporal artery–to-middle cerebral artery (STA-MCA) bypass in the revascularized hemisphere in the MCA territory (mean ± SD, −0.0005 ± 0.053 to 0.053 ± 0.046 %BOLD/mm Hg; P < .0001) and in the anterior cerebral artery territory (mean, 0.0015 ± 0.059 to 0.021 ± 0.052 %BOLD/mm Hg; P = .005). There was no difference in WM cerebrovascular reactivity in the ipsilateral posterior cerebral artery territory nor in the vascular territories of the nonrevascularized hemisphere (P < .05).CONCLUSIONS: Cerebral revascularization surgery is an effective treatment for reversing preoperative cerebrovascular reactivity deficits in WM. In addition, direct–STA-MCA bypass may prevent recurrence of preoperative symptoms.ACAanterior cerebral arteryBOLDblood oxygen level–dependentCVRcerebrovascular reactivityMMDMoyamoya diseasePCAposterior cerebral arteryPETCO2end-tidal partial pressure of CO2STAsuperficial temporal artery